Genome and pan-genome analysis of a new exopolysaccharide-producing bacterium Pyschrobacillus sp. isolated from iron ores deposit and insights into iron uptake - Najjari, Afef; Jabberi, Marwa; Chérif, Saïda Fatma; Cherif, Ameur; Ouzari, Hadda Imene; Linares-Pastén, Javier A.; Sghaier, Haitham (Frontiers in Microbiology, 2024)
We report the genome, pangenomic analysis, and exopolysaccharide characterisation of Psychrobacillus sp. NEAU-3TGS is a new species isolated from an iron ore deposit at the Tamra iron mine in northern Tunisia. NEAU-3TGS genome (4.48 Mb) had a mean GC content of 36%, 4,243 coding sequences and 14 RNA genes. Comparative genomic analysis within the nine validated species based on phylogenomic analysis and calculation of nucleotide identity (ANI) values (less than 95% for new species with all strains) confirmed that NEAU-3TGS represents a potential new species. Pangenomic analysis of the nine species and NEAU-3TGS strain revealed that Psychrobacillus genomic diversity represents an "open" pangenome model with 33,091 homologous genes, including 65 core, 3,738 shell and 29,288 cloud genes-notably—Psychrobacillus sp. NEAU-3TGS demonstrated the potential to produce exopolysaccharide (EPS) encoded by four genes, including one glycosyltransferase. Structural characterisation of EPS by attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) shows uronic acid and α-1,4-glycosidic bonds as dominant components of the EPS. X-ray diffraction (XRD) analysis revealed the presence of chitin, chitosan, and calcite CaCO3 and confirmed the amorphous nature of the EPS. Indeed, heavy metal bioabsorption assessment showed that EPS absorbs up to 95 % of iron, 88 % of lead and 70 % of copper and cadmium for an initial concentration of 1000 ppm. Genomic insights on iron acquisition and metabolism in Psychrobacillus sp. NEAU-3TGS showed that no genes involved in siderophore biosynthesis were found, and only the gene cluster FeuBCD and trilactone hydrolase genes involved in the uptake of siderophores, iron transporter and exporter were present. Molecular modelling and docking of FeuA (protein peptidoglycan siderophore-binding protein) and siderophores ferrienterobactine [Fe+3 (ENT)]-3 and ferribacillibactine [Fe+3 (BB)]-3 ligand revealed that [Fe+3 (ENT)]-3 binds to Phe122, Lys127, Ile100, Gln314, Arg215, Arg217, and Gln252. Almost the same for [Fe+3 (ENT)] -3 in addition to Cys222 and Tyr229, but not Ile100.To the best of our knowledge, this is the first report on the characterisation of EPS and the adsorption of heavy metals by Psychrobacillus species. The heavy metal removal capabilities may be advantageous for using these organisms in metal remediation.